Narrativas visuais e sonoras na ressignificação de saberes - Rosa, Elaine Isabel Souza da (2016)
The goal of this work is to demonstrate the value of students self-expression through visual and sound narratives, allowing an exploration of sense and reason. The work is focused on a participative action-research, developed with high school students, specifically grade 9th, in a total of 27 students from the public school system in the city of Santa Maria, RS. The research aims to answer the following question: What is the role of the individual in this socio-environmental context? This question leads to the search of a protagonist and co-authorship role in interpretation, creation and recreation of reality that fosters the development of autonomy, interdisciplinary and contextualization. This is achieved through the identification of themes using the research as a basis to build actions and find the answer related to the selected problem. The research was carried out in 2015 and its overall goal was to apply visual and oral expression and through them build perceptions and concepts that allows the expression of ideas and feelings, as well as establish actions through the use of mobile devices. The specific goals are: to identify environmental themes; to define the main environmental problems in the community we live; to come up with collaborative strategies to bring forth our reality for the better understanding of the environmental theme; to use the mobile phone as a supporter the collect and publish the data, to explore student s oral and visual expression through and to build strategies for the comprehension of the problem at hand as well their socialization with the local community. Mobile phones were used to register relevant data such as images, sound, testimonies, and also for internet research, proving that the use of technology in the classroom modifies the process of teaching and learning, giving value to the students and bringing new perspectives to the learning experience. The results obtained were: a lecture with the Veterinarian class from UFSM, the writing of a letter to the city hall informing them of the project underway in the school and in the community, as well as asking for support in the project s development. The writing of a final reflective text, the suggestions of solutions to the problem giving emphasis to the creation of a Facebook page to bring the groups suggestions together. The use of mobile phones, a device every day more present in our lives, is not only practical, multifunctional, portable and light, but is also allows faster access to information, which creates a link between the possibilities and conflicts that its use fosters inside the learning institutions.